2014
DOI: 10.1161/hypertensionaha.113.02838
|View full text |Cite
|
Sign up to set email alerts
|

Excess Pressure Integral Predicts Cardiovascular Events Independent of Other Risk Factors in the Conduit Artery Functional Evaluation Substudy of Anglo-Scandinavian Cardiac Outcomes Trial

Abstract: S ystolic and diastolic blood pressure (BP) are important modifiable risk factors for cardiovascular disease.1 Recently, there has been increased interest in the potential predictive value of other parameters derived from the BP waveform. The complex interactions between the heart and the arterial system cause distinctive changes in the BP waveform with aging and disease. Two basic concepts have been advanced to explain these changes: windkessel models and wave transmission models. Windkessel models describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 38 publications
5
102
4
Order By: Relevance
“…Indeed, such evidence was recently reported from the Conduit Artery Function Evaluation study, where excess pressure integral was shown to independently predict cardiovascular events. 10 The excess pressure waveform has also been consistently shown to bear striking resemblance to the flow velocity trace in the ascending aorta, 6,7,11,17 representative of LV stroke volume. 20 With regard to Figure 2, it is XP derived that first rapidly rises with aortic pressure, before AR direct and RP derived (ie, reservoir pressure) more gradually begin to increase as the aorta distends and volume increases.…”
Section: Aortic Reservoir and Excess Pressure: A Physiological Paradigmmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, such evidence was recently reported from the Conduit Artery Function Evaluation study, where excess pressure integral was shown to independently predict cardiovascular events. 10 The excess pressure waveform has also been consistently shown to bear striking resemblance to the flow velocity trace in the ascending aorta, 6,7,11,17 representative of LV stroke volume. 20 With regard to Figure 2, it is XP derived that first rapidly rises with aortic pressure, before AR direct and RP derived (ie, reservoir pressure) more gradually begin to increase as the aorta distends and volume increases.…”
Section: Aortic Reservoir and Excess Pressure: A Physiological Paradigmmentioning
confidence: 90%
“…6,8 Moreover, indices derived from this model were recently shown to predict cardiovascular events (fatal and nonfatal) and procedures independent from brachial BP and other conventional cardiovascular risk parameters (eg, age, sex, cholesterol, smoking, diabetes mellitus), including Framingham risk score, in an analysis of the Conduit Artery Function Evaluation study. 10 In accounting for the reservoir function of the aorta, 7,11 the reservoir-excess pressure model is founded on the basis that aortic BP can be separated into…”
mentioning
confidence: 99%
“…The results of the Conduit Artery Function Evaluation (CAFE) study, a substudy of the Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) have confirmed that central aortic pressure is a stronger predictor of stroke and CHD complications as compared to peripheral blood pressure (BP) in the brachial artery [31].…”
Section: Evaluation Of Arterial Stiffness In Patients With Bronchial mentioning
confidence: 99%
“…This leads to augmented BP and results in left ventricular hypertrophy due to the increased myocardial load. The reservoir pressure is highly correlated with changes in proximal aortic volume, and parameters from the reservoir wave can predict cardiovascular events and correlates with left ventricular mass [40,41,42]. The excess pressure integral is the difference between the measured BP waveform and reservoir pressure, and is a measure of the extra work needed by the left ventricle.…”
Section: Differences Between Central and Peripheral Bp Measurementmentioning
confidence: 99%